MMS Multipoint electric field observations of small‐scale magnetic holes - Katherine A. Goodrich; Robert E. Ergun; Victoria Wilder; James Burch; Roy Torbert; Yuri Khotyaintsev; Per‐Arne Lindqvist; Christopher Russell; Robert Strangeway; Werner Magnes; Daniel Gershman; Barbara Giles; et al. (Geophysical Research Letters)
Abstract Small‐scale magnetic holes (MHs), local depletions in magnetic field strength, have been observed multiple times in the Earth's magnetosphere in the bursty bulk flow (BBF) braking region. This particular subset of MHs has observed scale sizes perpendicular to the background magnetic field (B) less than the ambient ion Larmor radius (ρi). Previous observations by Time History of Events and Macroscale Interactions during Substorms (THEMIS) indicate that this subset of MHs can be supported by a current driven by the E × B drift of electrons. Ions do not participate in the E × B drift due to the small‐scale size of the electric field. While in the BBF braking region, during its commissioning phase, the Magnetospheric Multiscale (MMS) spacecraft observed a small‐scale MH. The electric field observations taken during this event suggest the presence of electron currents perpendicular to the magnetic field. These observations also suggest that these currents can evolve to smaller spatial scales.